Faces of exclusion: the “social,” the “digital” and “digital racism” in a decolonial critical essay - Lívia de Oliveira Mariano; Luciana de Santos Moura; Rodrigo Helder Paiani Mattos; Fabiana Pinto de Almeida Bizarria; Luciana Kind (Frontiers in Sociology)
This article addressed digital racism and exclusion from the decolonial perspective, explicitly concerning the possibilities of resistance to colonial structures. This argument was based on the discussion of intersectionality as a reference to the multiple combinations of exclusionary experiences expressed here through new forms of hierarchizing difference, understood from the perspective of social classification, as taught by Aníbal Quijano. We theoretically rehearsed the topic to broaden dialogs, conducting a reflective exercise that invites debate. Based on the notions of subjectivation processes emerging from this elaboration, we performed a propositional reflection, pointing to plural and collective solutions that rescue the memory and knowledge denied by coloniality. Furthermore, we suggest the rediscovery of local practices and values, as opposed to the adherence to standards established by remnants of colonization that are transmitted and reverberated in contemporary daily life.